The value of Technetium-99-Metastable-Ethylenedicysteine-eoxyglucose (⁹⁹ᴹTC-EC-DG) imaging in patients with Rheumatoid Arthritis - Evbuomwan, Osayande (University of the Free State, 2023)
Rheumatoid arthritis (RA) is a systemic inflammatory disease that is usually associated with synovitis that can lead to progressive joint damage if not managed appropriately. Prompt diagnosis and early treatment offer a good prognosis in patients with RA. However, treatment monitoring remains challenging for the rheumatologist as it is sometimes difficult to differentiate true remission from subclinical disease. Several modalities are available for assessing disease activity in patients with RA. This usually involves a combination of the clinical assessment of involved joints, laboratory and imaging investigations. Imaging with ultrasound (US) and magnetic resonance imaging (MRI) are considered to be among the most sensitive methods of assessing disease activity. However, these modalities are not without shortcomings. The aim of this study was to investigate the use of technetium-99-metastable ethylenedicysteine-deoxyglucose (⁹⁹ ͫ Tc-EC-DG) in the management of patients with RA. Using ⁹⁹ ͫ Tc-EC-DG to identify synovitis and offer prognostic information was investigated. Its usefulness in assessing treatment response compared to US and the diagnostic accuracy of identifying the disease compared to US was also investigated. A prospective study was conducted at the Department of Nuclear Medicine of the University of the Free State/Universitas Academic Hospital in Bloemfontein, South Africa. Twenty-two participants seen at the Rheumatology Unit of the Department on Internal Medicine, diagnosed with RA, were enrolled according to the American College of Rheumatology/ European League Against Rheumatism (ACR/EULAR) classification criteria. Participants were injected with 20–25 millicurie (mCi) of ⁹⁹ ͫ Tc-EC-DG. Flow, blood pool, whole body, delayed static, and SPECT/CT images were acquired. Known disease sites were qualitatively assessed for the intensity of uptake, and disease severity was graded (Grade 0–3). On the same day, US imaging of the most affected joints was performed in addition to blood samples being obtained from each participant for baseline C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), rheumatoid factor (RF) and anti-cyclic citrullinated peptide (anti-CCP) antibody titre. All imaging and laboratory investigations were performed at baseline, six weeks and six months follow-up after baseline findings in 20 of the participants. The median (interquartile range) age was 59 (49–68) years, and the majority (n=21; 95.5%) of patients were female. An abnormally increased uptake of ⁹⁹ ͫ Tc-EC-DG was noted in the majority of the sites of known disease, including unknown sites. SPECT/CT imaging localised tracer uptake specifically to the synovial space. Fourteen (63.6%) of the 22 participants had elevated RF and anti-CCP antibody titres. A significant correlation between higher grade uptake and increased levels of RF and anti-CCP antibodies (p=0.031) was observed. A total of 404 joints were evaluated by ⁹⁹ ͫ Tc-EC-DG and US imaging. The overall sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy of ⁹⁹ ͫ Tc-EC-DG SPECT/CT imaging were 86%, 60%, 61%, 85% and 73%, respectively, using US as the gold standard. A sensitivity of 100% was noted in the identification of synovitis in the carpal and knee joints. Disease activity in the distal interphalangeal (DIP) joints was not observed with either ⁹⁹ ͫ Tc-EC-DG or US imaging. The level of agreement between US and ⁹⁹ ͫ Tc-EC-DG imaging in assessing therapy response was 33.3 %, 11.6 % and 6.67 % for the knees, hands and wrist joints, respectively. ⁹⁹ ͫ Tc-EC-DG is a safe radiopharmaceutical that can effectively assess disease activity in the joints of patients with RA, with a strong correlation between high-grade disease on imaging and the presence of RF and anti-CCP antibodies. It has a high sensitivity in detecting synovitis when compared to US imaging. However, it has a poor correlation in the assessment of treatment response in comparison to US findings, which might be attributed to its ability to better detect subclinical disease. Using ⁹⁹ ͫ Tc-EC-DG offers facilities with only SPECT or SPECT/CT cameras an opportunity to investigate patients with RA.
Thesis (Ph.D.(Nuclear Medicine))--University of the Free State, 2023
Keywords: ⁹⁹ ͫ Tc-glucosamine; ⁹⁹ ͫ Tc-EC-DG; anti-cyclic citrullinated peptide; computed tomography; CT; diagnostic accuracy; Doppler ultrasound; EC-DG; Ethylenedicysteine-deoxyglucose; Magnetic resonance imaging; MRI; Radiolabelled; Radiopharmaceutical; Rheumatoid arthritis; Rheumatoid factor; Sensitivity; Specificity; single-photon emission computed tomography/ computed tomography; SPECT/CT; Ultrasound; US